Embryonic Exposure to Valproic Acid Impairs Social Predispositions of Newly-Hatched Chicks - Sgadò, Paola (Sci Rep, 2018)
Biological predispositions to attend to visual cues, such as those associated with face-like stimuli or with biological motion, guide social behavior from the first moments of life and have been documented in human neonates, infant monkeys and domestic chicks. Impairments of social predispositions have been recently reported in neonates at high familial risk of Autism Spectrum Disorder (ASD). Using embryonic exposure to valproic acid (VPA), an anticonvulsant associated to increased risk of developing ASD, we modeled ASD behavioral deficits in domestic chicks. We then assessed their spontaneous social predispositions by comparing approach responses to a stimulus containing a face configuration, a stuffed hen, vs. a scrambled version of it. We found that this social predisposition was abolished in VPA-treated chicks, whereas experience-dependent mechanisms associated with filial imprinting were not affected. Our results suggest a specific effect of VPA on the development of biologically-predisposed social orienting mechanisms, opening new perspectives to investigate the neurobiological mechanisms involved in early ASD symptoms.